Comparison of Immunohistochemical Expression of Epidermal Growth Factor Receptor in Benign and Malignant Salivary Gland Tumors - Khitab, Aysha; Alam, Sadaf; Nasir, Sabeen; Ali, Imad; Hanif, Maria; Malik, Mehreen (ADVANCES IN BASIC MEDICAL SCIENCES, 2022)
Objective: To compare the immunohistochemical expression of epidermal growth factor receptor (EGFR) in benign and malignant salivary gland tumors. Methodology: A total of 100 cases of benign and malignant salivary gland tumors (50 each) were retrieved from histopathology lab of Peshawar Medical College, Peshawar (PMC) and Pakistan Institute of Medical Sciences, Islamabad (PIMS). Their clinical information such as gender, age and site of tumor was recorded and Hemotoxylin and eosin examination was done to confirm the diagnosis. Total immunoreactivity score of EGFR expression was determined as the sum of the staining percentage and intensity. Results: Among 100 cases included in our study, EGFR immunopositivity was seen in 69% (n=69) of cases collectively of both Benign & Malignant Salivary Gland Tumors. Statistically, a strong correlation was observed between EGFR expression and salivary gland tumors (P≤0.05). Conclusion: This research concludes that malignant salivary gland tumors (MSGTs) show a higher EGFR expression. Positive EGFR expression seen in benign salivary gland tumors (BSGTs) might indicate their aggressive behavior, recurrence and epithelial proliferation especially in Pleomorphic adenoma cases. Key words: EGFR, Immunohistochemistry, Mucoepidermoid Carcinoma, Pleomorphic Adenoma, Salivary gland tumors